1997
DOI: 10.1364/josab.14.001625
|View full text |Cite
|
Sign up to set email alerts
|

Cancellation of photoinduced absorption in metal nanoparticle composites through a counterintuitive consequence of local field effects

Abstract: By applying the Maxwell Garnett model to gold nanoparticles in water we deduce a value of Im i (3) ϭ 1.1 ϫ 10 Ϫ7 esu for the imaginary part of the cubic susceptibility for gold corresponding to a Fermi smearing mechanism. We also demonstrate a sign reversal in the nonlinear absorption for gold particles in 1, 1Ј, 3, 3, 3Ј, 3Ј-hexamethylindotricarbocyanine iodide. Although the imaginary part of (3) is positive for each component by itself, remarkably the imaginary part of (3) is negative for the colloid as a wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 16 publications
(47 reference statements)
1
53
0
Order By: Relevance
“…At the plasmon resonance, multiphoton processes may be amplifi ed by the enhanced electric fi eld within or in proximity of metallic nanoparticles. For example, it has been observed that size-dependent third harmonic generation (THG) is feasible in gold nanoparticles [29,46,47] . It is interesting to note that THG is induced at the particle surface, with a nonlinear dipole proportional to the area of the sphere rather than to its volume [29] , due to the small skin depth of metals and the corresponding small fi eld penetration.…”
Section: Plasmonic Nanoantennas With Enhanced Nonlinear Responsementioning
confidence: 99%
“…At the plasmon resonance, multiphoton processes may be amplifi ed by the enhanced electric fi eld within or in proximity of metallic nanoparticles. For example, it has been observed that size-dependent third harmonic generation (THG) is feasible in gold nanoparticles [29,46,47] . It is interesting to note that THG is induced at the particle surface, with a nonlinear dipole proportional to the area of the sphere rather than to its volume [29] , due to the small skin depth of metals and the corresponding small fi eld penetration.…”
Section: Plasmonic Nanoantennas With Enhanced Nonlinear Responsementioning
confidence: 99%
“…From Eq. (11) or (12) it is obvious that dielectric confinement induces a local field correction to the nonlinear response of metal nanoparticles, which has several significant consequences [44,56,57]. Since both f and (3) m χ are complex quantities, the medium third-order nonlinear response may present unexpected values.…”
Section: 4mentioning
confidence: 99%
“…58 59 After focusing on the effect of dielectric confinement on the third-order nonlinear optical response, let us glance at the intrinsic nanoparticle susceptibility. Surprisingly, very few theoretical works have been devoted to the value of (3) m χ in noble metal nanoparticles [57,58] after the pioneering studies of Flytzanis' group who identified and evaluated the different electronic contributions [47,48,56,59]. They first distinguished two pure nonlinear origins corresponding to intraband and interband transitions as in the linear case.…”
Section: 4mentioning
confidence: 99%
“…Local-field effects were included in off-resonant frequency domain susceptibilities to resolve discrepancies of the calculated absolute magnitude with experiment. [4][5][6][7] In the time domain, they were required when unexpected signals showed that the time ordering of short pulses is scrambled by molecules with long-lived polarization (slow dephasing). 8,9 Various other experimental observables that are altered by local-field effects, such as the transmission/reflection of a thin film 10 and the Rabi oscillations of a quantum dot 11 have been identified.…”
Section: Introductionmentioning
confidence: 99%